Excellent sheep : the miseducation of the American elite and the way to a meaningful life - Deresiewicz, William, 1964- (Free Press, 2014)
"A groundbreaking manifesto for people searching for the kind of insight on leading, thinking, and living that elite schools should be--but aren't--providing"--